Synthesis and utility of N-boryl and N-silyl enamines derived from the hydroboration and hydrosilylation of N-heteroarenes and N-conjugated compounds - Cao, Vinh Do; Joung, Seewon (Frontiers in Chemistry, 2024)
Catalytic hydroboration and hydrosilylation have emerged as promising strategies for the reduction of unsaturated hydrocarbons and carbonyl compounds, as well as for the dearomatization of N-heteroarenes. Various catalysts have been employed in these processes to achieve the formation of reduced products via distinct reaction pathways and intermediates. Among these intermediates, N-silyl enamines and N-boryl enamines, which are derived from hydrosilylation and hydroboration, are commonly underestimated in this reduction process. Because these versatile intermediates have recently been utilized in situ as nucleophilic reagents or dipolarophiles for the synthesis of diverse molecules, an expeditious review of the synthesis and utilization of N-silyl and N-boryl enamines is crucial. In this review, we comprehensively discuss a wide range of hydrosilylation and hydroboration catalysts used for the synthesis of N-silyl and N-boryl enamines. These catalysts include main-group metals (e.g., Mg and Zn), transition metals (e.g., Rh, Ru, and Ir), earth-abundant metals (e.g., Fe, Co, and Ni), and non-metal catalysts (including P, B, and organocatalysts). Furthermore, we highlight recent research efforts that have leveraged these versatile intermediates for the synthesis of intriguing molecules, offering insights into future directions for these invaluable building blocks.